A New Oval Advancement Flap Design for Reconstruction of Pilonidal Sinus Defect - Arpaci, Enver; Altun, Serdar; Orhan, Erkan; Eyuboglu, Atilla; Ertas, Nilgun Markal (Springer, 2018)
Backgrounds Pilonidal sinus is a common chronic disease of the sacrococcygeal region. Although many surgical methods have been described for treating pilonidal sinus disease, controversy still exists as to the best surgical technique. The aim of this study is to present a new modified advancement flap technique named omega flap for the treatment of pilonidal sinus disease. Materials and methods This study included 18 patients with pilonidal sinus who were treated between March 2012 and August 2014. All cases underwent oval excision and omega advancement flap reconstruction. Defect size, postoperative complications, postoperative pain, painless sitting time, patient satisfaction and recurrence were evaluated retrospectively. Results All patients were discharged on the first postoperative day. There was no flap necrosis. No recurrence and no major complication were observed during follow-up period. The outcomes were also satisfactory regarding functionally and aesthetically, and the patients were satisfied with the results. Conclusions Presented method has a different geometry than classical advancement flap methods. Our technique provides two-layered repair with minimal tension and off-midline closure for the reconstruction of pilonidal sinus defect. It is easily performed, reliable, associated with no recurrens and good aesthetic results.
Keywords: Limberg Transposition Flap; V-Y Flap; Surgical-Treatment; Disease; Surgery; Closure